Blood pressure and the risk of rebleeding and delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage - Gathier, Celine S.; Zijlstra, IJsbrand A.J.; Rinkel, Gabriel J.E.; Groenhof, T. Katrien J.; Verbaan, Dagmar; Coert, Bert A.; Müller, Marcella C.A.; van den Bergh, Walter M.; Slooter, Arjen J.C.; Eijkemans, Marinus J.C. (Journal of critical care, 2022)
Blood pressure is presumably related to rebleeding and delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (aSAH) and could serve as a target to improve outcome. We assessed the associations between blood pressure and rebleeding or DCI in aSAH-patients. In this observational study in 1167 aSAH-patients admitted to the intensive care unit (ICU), adjusted hazard ratio's (aHR) were calculated for the time-dependent association of blood pressure and rebleeding or DCI. The aHRs were presented graphically, relative to a reference mean arterial pressure (MAP) of 100 mmHg and systolic blood pressure (sBP) of 150 mmHg. A MAP below 100 mmHg in the 6, 3 and 1 h before each moment in time was associated with a decreased risk of rebleeding (e.g. within 6 h preceding rebleeding: MAP = 80 mmHg: aHR 0.30 (95% confidence interval (CI) 0.11–0.80)). A MAP below 60 mmHg in the 24 h before each moment in time was associated with an increased risk of DCI (e.g. MAP = 50 mmHg: aHR 2.59 (95% CI 1.12–5.96)). Our results suggest that a MAP below 100 mmHg is associated with decreased risk of rebleeding, and a MAP below 60 mmHg with increased risk of DCI. •In our observational study of 1167 SAH patients, MAP < 100 mmHg was associated with decreased risk of rebleeding.•MAP < 60 mmHg was associated with increased risk of delayed cerebral ischemia (DCI).•Whether optimizing MAP values will in fact prevent rebleeding or DCI could be subject of future prospective research.